Functional Neuronal Differentiation of Injury-Induced Muscle-Derived Stem Cell-Like Cells with Therapeutic Implications - Kinga Vojnits (Nature Portfolio, 2017)
Abstract Mammalian skeletal muscles contain a number of heterogeneous cell populations. Our previous study characterized a unique population of myogenic lineage stem cells that can be isolated from adult mammalian skeletal muscles upon injury. These injury-induced muscle-derived stem cell-like cells (iMuSCs) displayed a multipotent state with sensitiveness and strong migration abilities. Here, we report that these iMuSCs have the capability to form neurospheres that represent multiple neural phenotypes. The induced neuronal cells expressed various neuron-specific proteins, their mRNA expression during neuronal differentiation recapitulated embryonic neurogenesis, they generated action potentials, and they formed functional synapses in vitro. Furthermore, the transplantation of iMuSCs or their cell extracts into the muscles of mdx mice (i.e., a mouse model of Duchenne Muscular Dystrophy [DMD]) could restore the morphology of their previously damaged neuromuscular junctions (NMJs), suggesting that the beneficial effects of iMuSCs may not be restricted to cell restoration alone, but also due to their transient paracrine actions. The current study reveals the essential role of iMuSCs in the restoration of NMJs related to injuries and diseases.